2009
DOI: 10.1021/ja9021304
|View full text |Cite
|
Sign up to set email alerts
|

Proton NMR of 15N-Choline Metabolites Enhanced by Dynamic Nuclear Polarization

Abstract: Dynamic Nuclear Polarization (DNP) by the so-called 'dissolution' procedure 1 is rapidly gaining momentum as a novel method to enhance weak nuclear magnetic resonance (NMR) signals from molecular tracers, so that one can visualize their biodistribution and metabolism in ViVo. 2 The major limitation of the technique arises from the short lifetimes of hyperpolarized spin states in liquids. In particular, longitudinal relaxation times T 1 of protons in solutions of biomolecules are too short to allow for transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
133
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 110 publications
(138 citation statements)
references
References 13 publications
1
133
0
4
Order By: Relevance
“…40,41 In vivo relaxation times showed a decrease compared with the in vitro values, which can be explained by the fact that the relaxation times of metabolite are likely to be influenced by the microenvironment. 43 In addition, the in vivo relaxation times exhibited a deviation from the standard mono-exponential decay, with a very fast decay (6 AE 1.5 s) during the first seconds, followed by a slower decay afterwards (126 AE 15 s).…”
Section: This Journal Is C the Owner Societies 2010mentioning
confidence: 95%
See 1 more Smart Citation
“…40,41 In vivo relaxation times showed a decrease compared with the in vitro values, which can be explained by the fact that the relaxation times of metabolite are likely to be influenced by the microenvironment. 43 In addition, the in vivo relaxation times exhibited a deviation from the standard mono-exponential decay, with a very fast decay (6 AE 1.5 s) during the first seconds, followed by a slower decay afterwards (126 AE 15 s).…”
Section: This Journal Is C the Owner Societies 2010mentioning
confidence: 95%
“…38 To date, besides optically polarized 3 He and 129 Xe, 39 6 Li is the only hyperpolarized nucleus besides 13 C that has been reported to be detected in vivo. 38 Two recent studies reported remarkably long in vitro longitudinal relaxation times for 15 N Cho, 40,41 suggesting that hyperpolarized 15 N Cho could be a suitable candidate for in vivo experiments.…”
Section: Introductionmentioning
confidence: 99%
“…
In vivo localized and fully adiabatic homonuclear and heteronuclear polarization transfer experiments were designed and performed in the rat brain at 9.4 T after infusion of hyperpolarized sodium [1,[2][3][4][5][6][7][8][9][10][11][12][13] C 2 ] and sodium [1-13 C] acetate. The method presented herein leads to highly enhanced in vivo detection of short-T 1 13 C as well as attached protons.
…”
mentioning
confidence: 99%
“…This is particularly challenging in vivo, as the spectral resolution in tissues is more limited than in vitro. Recently, polarization transfer methods were proposed for in vitro DNP-enhanced high-resolution applications in liquid-state NMR allowing the enhancement of short-T 1 nuclear spins via J-coupling-mediated transfer from the large spin polarization of the long-T 1 nuclear spins in various molecules (7)(8)(9).In this article, we present an in vivo hyperpolarization transfer sequence to enhance the signal of short-T 1 nuclear spins. The proposed method allows for the in vivo localized detection of aliphatic carbons or even protons and thus offers the possibility to increase the spectral resolution or obtain additional information on the chemical environment of specific nuclear spins in biomedical hyperpolarized MR experiments.…”
mentioning
confidence: 99%
“…For instance, the long T 1 ( 15 N) E 189 s of partially-deuterated choline (CD 3 ) 3 15 N + CH 2 CH 2 OHÁCl À in D 2 O can be used to preserve the enhanced 15 N polarisation during the voyage, prior to transferring the magnetisation from 15 N to 1 H for detection. 6 Non-equilibrium populations of nuclear spins can be stored in the form of long-lived states (LLS) with lifetimes T LLS that can last much longer than the longitudinal 'spin-lattice' relaxation times T 1 . [10][11][12] These states are largely immune to relaxation effects because of the spin-permutation symmetry of the system.…”
mentioning
confidence: 99%